Osteology of Physalaemus nattereri (Anura: Leptodactylidae) with comments on intraspecific variation - Fratani, Jéssica; Woitovicz-Cardoso, Manoela; Lourenço, Ana Carolina Calijorne [UNESP] (Magnolia Press, 2017)
The cranium, postcranium, and osteological variation of Physalaemus nattereri (Steindachner) are described. The main sources of variation involve the degree of mineralization of the nasal capsule and the lengths of dermal skull bones (e.g., vomer, sphenethmoid, and neopalatine). Osteologically, P. nattereri differs from its congeners by the anterior placement of the jaw articulation (which lies anterior to the intersection between the alae and cultriform process of parasphenoid), and by the separation of the frontoparietals from the anterior margins of exoccipitals. Descriptions of the nasal capsule, the auditory apparatus, and the iliosacral articulation are presented for the first time for this species. One putative morphological synapomorphy is presented for the P. signifer Clade.
Keywords: Amphibia; Anatomy; Morphology; Nasal capsule; Skeleton